TRADUTOR E INTÉRPRETE DE LÍNGUA DE SINAIS (TILS): COMPREENSÃO SEMÂNTICO-PRAGMÁTICA DE TERMINOLOGIAS JURÍDICAS - Reis, Elizabeth Martins dos (2022)
In the current scenario, we find Sign Language Translators and Interpreters (TILS) who work directly in community contexts, considered essential rights for the social sphere of the deaf community, and with the use of Brazilian Sign Language (Libras). However, the role of TILS in the legal context is what has awakened new scientific research, which seeks to theoretically support the task of translation and/or interpretation in this field. In the legal context, magistrates and legal practitioners use specific vocabularies and terminologies of the legal scope, and there may often be a gap in understanding and/or gaps in cognitive understanding arising from the legal text, during the interpretive act, in that many times TILS does not have prior knowledge of the content of the subject. Legal terms-concepts are polysemic, and when applied to Libras, they require Cognitive Efforts (GILE, 2005; MACHADO, 2017), based on the Idealized Cognitive Models, which deals with the subtheory of the theoretical framework of Cognitive Linguistics (LAKOFF, 1986). In this way, the research of this dissertation aims to analyze the semantic-pragmatic implications that may arise from a simultaneous interpretation of texts recorded in Portuguese (oral modality) with legal terminologies/vocabularies, thus describing, as a linguistic-cognitive phenomenon that occurs during the simultaneous interpretive task. The theoretical contribution is those that directly discuss Translation Studies (HURTADO ALBIR, 2005; BASSNET, 2005) and Interpretation Studies, especially in the community context (POCHHACKER, 2016). However, the research explores references in the area of Libras, correlated to the legal context (MACHADO, 2012/2017; SANTOS, 2016). The proposal is to order to respond to the hypotheses that arise in the face of the difficulties and complexities of TILS in relation to the understanding of terminology and legal-concepts regarding the task of simultaneous interpretation of TILS to texts with high legal content, such as the legalese of the judicial system. The research is characterized by a qualitative-quantitative methodology, followed by procedures of a controlled situation, using excerpts from a text taken from a criminal legal sentence. The terms-concepts- legal chosen for the application of the research, form: criminal body, criminal responsibility, legitimate defense, procedural instruction, dose the penalty, criminal background, liability, base penalty, and detention. The data collection used was carried out remotely, by google meet, and soon after, we performed the transcription directly in the ELAN software of the simultaneous interpretations with 10 experienced TILS and CODA's. The results obtained from the research confirm the challenges involved in the cognitive activity of TILS, in situations of high conceptual complexity regarding the understanding of terminology and/or legal concepts involved in the task of simultaneous interpretation, and requires a broad discussion on the understanding of TILS who do not know the protocols of Law, and consequently, due to the lack of knowledge, which occurs from the source language (LP) to the target language Libras.